Reconsidering REDD+ : authority, power, and law in the green economy / Julia Dehm, La Trobe University. - Dehm, Julia (Cambridge studies on environment, energy and natural resource governance., 2021)
In Reconsidering REDD+: Authority, Power and Law in the Green Economy, Julia Dehm provides a critical analysis of how the Reducing Emissions from Deforestation and Forest Degradation (REDD+) scheme operates to reorganise social relations and to establish new forms of global authority over forests in the Global South, in ways that benefit the interests of some actors while further marginalising others. In accessible prose that draws on interdisciplinary insights, Dehm demonstrates how, through the creation of new legal relations, including property rights and contractual obligations, new forms of transnational authority over forested areas in the Global South are being constituted. This important work should be read by anyone interested in a critical analysis of international climate law and policy that offers insights into questions of political economy, power, and unequal authority.